Life imprisonment and prison regime stability - Cullen, James Eric (1993)
This research examines the nature of life imprisonment in the British Prison Service with particular reference to the related issues of indeterminacy, regime stability and the ethical implications of current policies. Samples of over 400 inmates and 90 staff in 6 adult and young offender prisons were involved. The author addressed questions concerning the extent to which lifers are distinguishable from non-lifers, produce a stabilising effect on the regimes of their prisons and pay some price as a consequence. The prisons concerned are among those with the highest security classifications which have particular concern not to experience riots or other major acts of concerted indiscipline. Questions which followed from these were to do with both the efficacy and the ethics of either concentrating most lifers, as at present, separating them or determining allocation on a different basis. This cost-benefit perspective also explored the views of Prison Service policy-makers, prison Governors and local staff. The results of interviews, questionnaires and official records are analysed to discern how they bear on the research questions. Final commentary and recommendations are presented within the wider context of the recent (1991) Criminal Justice Bill